Methods of Solving Differential Equations - Jumaeva, Shakhnoza (Science and Education, 2024)
A variety of physical processes, including heat conduction, wave propagation, fluid movement, and quantum physics, are fundamentally described by partial differential equations, or PDEs. Multiple variable functions and their partial derivatives are involved in these equations. Based on the number of independent variables, the type of boundary and initial conditions, and the nature of the equations (linear or nonlinear), PDEs can be categorized.